2017
DOI: 10.1177/1403494817695911
|View full text |Cite
|
Sign up to set email alerts
|

Decennial trends and inequalities in healthy life expectancy: The HUNT Study, Norway

Abstract: The increase in total life expectancy was accompanied by an increasing number of years spent in good self-rated health but more years with longstanding limiting illness. This suggests increasing health care needs for people with chronic diseases, given an increasing number of elderly. Socioeconomic health inequalities remain a challenge for increasing pensioning age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…This is consistent with the evidence of a reduction in the proportion of life spent without disability in the UK. This pattern was also observed in: all high-income countries combined in the Global Burden of Disease studies, [36][37][38] Norway, 26 Belgium, 19 Japan 22 23 and the USA 33 for all, and in Switzerland 31 and Sweden 30 for men but not women. This points to evidence of an expansion of disability in a number of high-income countries, although not always consistently between men and women.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…This is consistent with the evidence of a reduction in the proportion of life spent without disability in the UK. This pattern was also observed in: all high-income countries combined in the Global Burden of Disease studies, [36][37][38] Norway, 26 Belgium, 19 Japan 22 23 and the USA 33 for all, and in Switzerland 31 and Sweden 30 for men but not women. This points to evidence of an expansion of disability in a number of high-income countries, although not always consistently between men and women.…”
Section: Resultsmentioning
confidence: 58%
“…16 Two of the UK studies were ONS reports. 15 16 The remaining studies reported trends in Belgium, [17][18][19] Canada, 20 Denmark, 21 Japan, 22 23 the Netherlands, 24 25 Norway, 26 Republic of Korea, 27 28 Sweden, 29 30 Switzerland 31 and the USA. [32][33][34][35] Three Global Burden of Disease studies were included, which reported trends across multiple countries, and high-income countries combined.…”
Section: Resultsmentioning
confidence: 99%
“…The compression of morbidity hypothesis originally proposed by Fries [1] stated that better health care, an active lifestyle, and advances in preventive health behavior would lead to increased active life expectancy and decreasing duration of morbidity and disability in the population. In support of this assumption several studies revealed a significant reduction in proportions of functional impairment and also increases of disability-free life expectancy and expected lifetime in good self-rated health (SRH) [2][3][4][5][6][7][8]. Pointing into the same direction, German studies reported improved SRH over time particularly in the elder population [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%
“…An essential precondition for this implementation is sufficiently good health and wellbeing of the elder working population. However, while there is some evidence of increasing healthy life expectancy [2,3], little is known on the possible rise of healthy working life expectancy, meaning the time spent in both work and good health [29]. Thus, we focused on individuals aged 50-70 years who are most directly affected by the pension policy.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, progress in medicine has been exceptional. New diagnostic procedures, more in‐depth understanding of pathophysiology, and new treatment options have led to a steady increase in life expectancy in North America and Europe, with a growing number of elderly patients with polypharmacy. Thus, it is becoming more difficult to avoid medication errors .…”
mentioning
confidence: 99%